HUBUNGAN PENGETAHUAN DAN SIKAP IBU HAMIL TENTANG KEPATUHAN MENGKONSUMSI TABLET FE UNTUK MENCEGAH ANEMIA PADA KEHAMILAN DI KLINIK JULIANA MEDAN TAHUN 2020 - KAMALIAH . (LP2MTBM MAKARIOZ, 2021)
According to the WHO, maternal mortality is very high. About 830 women die from pregnancy or childbirth complicationsworldwide every day. It is estimated that in 2015, about 303,000 women died during and after pregnancy and childbirth.Almost all of these deaths occur and most can be prevented, with the concern of health workers and the community itself.This study aims to find out the Relationship of Knowledge and Attitudes of Pregnant Women About Adherence Taking Fetablets to prevent anemia in Pregnancy at Juliana Clinic in 2020. This study is descriptive analytical with a cross sectionalapproach, where the entire population is sampled, namely pregnant women as many as 35 people. Analyze the data usingthe chi-square statistical test. The results showed that of the 35 respondents the majority who had good knowledge as manyas 16 respondents (45.71%) had a positive attitude as many as 13 respondents (37.14%, while a minority of knowledgeablerespondents quite 7 respondents (20%) had a positive attitude 3 respondents (8.5%). From the statistical test using the chisquaretest obtained a value of p = 0.10. where p<005 so that Ha is accepted and Ho is rejected which means there is asignificant relationship between knowledge and attitude of pregnant women about compliance with taking Fe tablets inpreventing anemia in pregnancy at Juliana Medan Clinic in 2020. It is recommended on the implementation of healthservices to improve the quality of health services by providing counseling to pregnant women, especially about compliancewith taking Fe tablets.